Novel hypoglycemic injury mechanism: N-methyl-D-aspartate receptor-mediated white matter damage - Yang, Xin; Hamner, Margaret A.; Brown, Angus M.; Evans, Richard D.; Ye, Zu-Cheng; Chen, Shengdi; Ransom, Bruce R. (Annals of Neurology, 2014)
Objective: Hypoglycemia is a common adverse event and can injure central nervous system (CNS) white matter (WM). We determined if glutamate receptors were involved in hypoglycemic WM injury. Methods: Mouse optic nerves (MON), CNS WM tracts, were maintained at 37°C with oxygenated artificial cerebrospinal fluid (ACSF) containing 10 mM glucose. Aglycemia was produced by switching to 0 glucose ACSF. Supra-maximal compound action potentials (CAPs) were elicited using suction electrodes and axon function was quantified as the area under the CAP. Amino acid release was measured using HPLC. Extracellular [lactate] was measured using an enzyme electrode. Results: About 50% of MON axons were injured after 60 min of aglycemia (90% after 90 min); injury was not affected by animal age. Blockade of NMDA-type glutamate receptors improved recovery after 90 min of aglycemia by 250%. Aglycemic injury was increased by reducing [Mg2+]o or increasing [glycine]o, and decreased by lowering pHo, expected results for NMDA receptor-mediated injury. Extracellular pH increased during aglycemia, due to a drop in [lactate-]o. Aglycemic injury was dramatically reduced in the absence of [Ca2+]o. Extracellular aspartate, a selective NMDA receptor agonist, increased during aglycemia. Interpretation: Aglycemia injured WM by a unique excitotoxic mechanism involving NMDA receptors (located primarily on oligodendrocytes). During WM aglycemia, the selective NMDA agonist, aspartate, is released, probably from astrocytes. Injury is mediated by Ca2+ influx through aspartate-activated NMDA receptors made permeable by an accompanying alkaline shift in pHo caused by a fall in [lactate-]o. These insights have important clinical implications.